Analisis Sosiologis Terhadap Peranan Keluarga Dalam Menumbuhkan Pengetahuan Agama Katolik Di Paroki Santo Yoseph Poka-Rumahtiga - Samponu, Leonora; Refo, Ignasius SS. (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2024)
This study aims to analyse the role of family in fostering Catholic religious knowledge for children’s personality development using George Herbert Mead’s sociological theory. Mead believes that the formation of individual personality is inseparable from social interactions that take place in the family environment. Through the concepts of “self” and “generalized other”, family, as the child’s closest social environment, plays an important role in the socialization process of Catholic religious values and teachings. This article employs a qualitative method by interviewing several Catholic families in Saint Joseph Parish, Poka-Rumahtiga. The results showed that families, especially parents, have a central role in introducing, teaching, and instilling Catholic religious knowledge and practices to children. This process occurs through symbolic interactions between children and parents and other family members. Children then develop self-understanding (self) and internalize the role of “others” (generalized other) in the context of Catholic religious teachings, which ultimately shapes children’s personality and morality in accordance with Catholic values